2004
DOI: 10.1152/jn.01021.2003
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Visually and Memory-Guided Saccades Induced by Electrical Stimulation of the Monkey Frontal Eye Field. I. Suppression of Ipsilateral Saccades

Abstract: When a saccade occurs to an interesting object, visual fixation holds its image on the fovea and suppresses saccades to other objects. Electrical stimulation of the frontal eye field (FEF) has been reported to elicit saccades, and recently also to suppress saccades. This study was performed to characterize properties of the suppression of visually guided (Vsacs) and memory-guided saccades (Msacs) induced by electrical stimulation of the FEF in trained monkeys. For any given stimulation site, we determined the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(62 citation statements)
references
References 56 publications
5
55
2
Order By: Relevance
“…Stimulation of the most rostral part of the SC suppressed saccades in bilateral directions, with predominant suppression of ipsilateral saccades (Munoz and Wurtz 1993b;Paré and Guitton 1994), and suppressed both Vsacs and Msacs (Munoz and Wurtz 1993b). Burman and Bruce (1997) reported that stimulation of the FEF mainly suppressed contraversive saccades and effectively suppressed Msacs but not Vsacs, whereas our previous study showed that FEF stimulation suppressed the initiation of ipsiversive saccades of both Vsacs and Msacs at low thresholds (Izawa et al 2004). Although the preceding discrepancies have not yet been resolved, these suppressive effects of FEF stimulation on the generation of saccades may contribute to maintaining fixation on a target of interest by preventing saccades to other targets in the visual field.…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…Stimulation of the most rostral part of the SC suppressed saccades in bilateral directions, with predominant suppression of ipsilateral saccades (Munoz and Wurtz 1993b;Paré and Guitton 1994), and suppressed both Vsacs and Msacs (Munoz and Wurtz 1993b). Burman and Bruce (1997) reported that stimulation of the FEF mainly suppressed contraversive saccades and effectively suppressed Msacs but not Vsacs, whereas our previous study showed that FEF stimulation suppressed the initiation of ipsiversive saccades of both Vsacs and Msacs at low thresholds (Izawa et al 2004). Although the preceding discrepancies have not yet been resolved, these suppressive effects of FEF stimulation on the generation of saccades may contribute to maintaining fixation on a target of interest by preventing saccades to other targets in the visual field.…”
Section: Introductionmentioning
confidence: 84%
“…Experiments were performed in two male Japanese monkeys (Macaca fuscata) that were also used in the preceding article (Izawa et al 2004). Monkeys were prepared for the experiments using the same procedures and the same series of fixation, visually guided, and memory-guided saccade tasks described in the preceding article (Izawa et al 2004).…”
Section: E T H O D Smentioning
confidence: 99%
See 3 more Smart Citations